Pengaruh Kualitas Pelayanan dan Religiusitas Terhadap Masyarakat dalam Bertransaksi dengan Bank Syariah Mandiri Pariaman - Syamsurizal, Syamsurizal; A, Abdur Rahim; Marseli, Anisa; Suwarni, Desi (Institut Agama Islam Sumatera Barat Pariaman, 2021)
This study supports the three alternative hypotheses developed that prove that service quality and religiosity simultaneously (together) have a significant effect on people's decisions about making transactions at Bank Syariah Mandiri, Pariaman Branch. This study aims to determine the factors that influence public decisions to transact at Bank Mandiri Syariah Pariaman, which is limited to the quality of service and religiosity. The population in this study were customers of Bank Syariah Mandiri Pariaman with a total sample size of 60 respondents. Where the sampling technique used is accidental sampling. In order to test the hypothesis, the t, f and r tests were carried out. The results showed that the factors of service quality and religiosity have an effect on people's decisions in making transactions at Bank Syariah Mandiri Pariaman. The contribution of the influence of service quality and religiosity variables on people's decisions to transact at Bank Syariah Mandiri Pariaman is 33.4%, while the rest (100% -33.4% = 66.6%) is the influenced by other variables that are not included in this research model.